Independent Origin of XY and ZW Sex Determination Mechanisms in Mosquitofish Sister Species. Issue 1 (1st January 2020) - Kottler, Verena A; Feron, Romain; Nanda, Indrajit; Klopp, Christophe; Du, Kang; Kneitz, Susanne; Helmprobst, Frederik; Lamatsch, Dunja K; Lopez-Roques, Céline; Lluch, Jerôme; Journot, Laurent; Parrinello, Hugues; et al.
Abstract: Fish are known for the outstanding variety of their sex determination mechanisms and sex chromosome systems. The western ( Gambusia affinis ) and eastern mosquitofish ( G. holbrooki ) are sister species for which different sex determination mechanisms have been described: ZZ/ZW for G. affinis and XX/XY for G. holbrooki . Here, we carried out restriction-site associated DNA (RAD-) and pool sequencing (Pool-seq) to characterize the sex chromosomes of both species. We found that the ZW chromosomes of G. affinis females and the XY chromosomes of G. holbrooki males correspond to different linkage groups, and thus evolved independently from separate autosomes. In interspecific hybrids, the Y chromosome is dominant over the W chromosome, and X is dominant over Z. In G. holbrooki, we identified a candidate region for the Y-linked melanic pigmentation locus, a rare male phenotype that constitutes a potentially sexually antagonistic trait and is associated with other such characteristics, e.g., large body size and aggressive behavior. We developed a SNP-based marker in the Y-linked allele of GIPC PDZ domain containing family member 1 ( gipc1 ), which was linked to melanism in all tested G. holbrooki populations. This locus represents an example for a color locus that is located in close proximity to a putative sex determiner, and most likely substantially contributed to the evolution of the Y.